Garrido, Juan Manuel. On Time, Being and Hunger. Challenging the Traditional Way of Thinking Life - Nicolás Parra (Ideas y Valores)
Garrido, Juan Manuel. On Time, Being and Hunger. Challenging the Traditional Way of Thinking Life. New York: Fordham University Press, 2012.